Do satisfied customers loyal? : Unravelling the role of trust in the ‘High Touch’ purchasing context / Rosidah Musa - Musa, Rosidah (Universiti Teknologi MARA Cawangan Pahang, 2006)
Theoretically, satisfaction should be positively linked to customer loyalty but it is difficult to observe because most customer satisfaction surveys rely on intentional behaviour data rather than actual behaviour. In response to this issue, a follow-up study was set to validate an integrative framework which include overall satisfaction, trust and simultaneously incorporates not only attitudinal loyalty but behavioural loyalty construct. Specifically, this study aims to examine the hypothesised linear relationship between satisfaction – attitudinal loyalty, satisfaction – behavioural loyalty and attitudinal loyalty – behavioural loyalty paths. What is more, the researcher also endeavours to explore the role of trust in the satisfaction – attitudinal loyalty – behavioural loyalty link, thus distinctively differentiated it from the existing model. To test the hypothesised links among the constructs in the framework, Structural Equation Modelling (AMOS programme) and subsequently the moderating effect of trust in the satisfaction – attitudinal loyalty – behavioural loyalty chain was determined by two-way ANOVA. The findings are important to the development of marketing theory and evidence of the plausibility of the present model suggests the need for further investigation and validation in other research contexts and across other countries.